In Vivo and In Vitro Study of the Genetic Effects of Cabergoline Drug - Altaee, Maha Fakhry; Abed, Reema Mohammed; Samawi, Farah Th. (Iraqi Journal of Science, 2021)
This study aimed to stand on genetic effects important of cabergoline drug. This toxic effect was evaluated for three different doses (0.05, 0.1, 0.5 mg/ml) in comparison with control (PBS/ phosphate buffer saline) both in vivo and in vitro. In vivo study involved the cytogenetic evaluation of cabergoline in mice by examination of mitotic index percentage (MI), micronucleus formation (MN) and chromosomal aberrations. Result indicated that all the tested doses cause significant reduction in MI percentage, while significant rise was seen with both MN formation and all studied chromosomal aberrations. While in vitro study involved measuring the effect of cabergoline on normal cell line (REF/ Rat embryonic fibroblast) by studing cell viability through MTT assay and a TP53 codon 72 polymorphism (rs1042522) through (PCR-RFLP). Results recorded that cabergoline caused high proliferation of normal cells at all doses and p53 polymorphism showed that the Arg allele yielding two fragments 213 and 140 bp after cleaving with BstuI,, while the Pro allele had a single 353 bp band because it did not cleaved by BstuI. In conclusion and according to the results care should be taken while obtaining cabergoline as a results of its genetic side effects.